إقتصاد المعرفة ومساهمته في تفعيل التنمية الإقتصادية والإجتماعية في الجزائر - أيمن فريد; عبد المالك مهري (My University, 2018)
تهدف هذه الدراسة الى تبيين مدى مساهمة الإقتصاد المعرفي في تفعيل التنمية الإقتصادية والإجتماعية في الجزائر، حيث جاءت مهيكلة في محورين رئيسيين يخدمان الإشكالية المطروحة والتي ترتكز حول المدى الذي وصلت إليه الجزائر بخصوص إقتصاد المعرفة؟ وما تأثير ذلك على التنمية الإقتصادية والإجتماعية فيها؟ وقد توصلت الدراسة إلى جملة من النتائج لعل أبرزها الانخفاض المستمر في مستوى التعليم بالجزائر وتدني مستوى البحث والتطوير وظهور الطابع البيروقراطي على ما هو مستخدم منها، بالإضافة طرد الموارد البشرية وفي مقدمتها الكفاءات العلمية التي هي لب الإقتصاد المعرفي. فضلا عن غياب إستراتيجية صناعة محتوى المعلومات التي تعتبر أهم مقومات مجتمع المعلومات. الكلمات المفتاحية: المعرفة، الجزائر، التعليم، التنمية، المجتمع، الإقتصاد. Abstract: This study aims to demonstrate the contribution of the knowledge economy to the activation of economic and social development in Algeria, which was structured in three main axes that serve the problem which is based on the extent of Algeria's knowledge economy. What impact does this have on economic and social development? The study found a number of results, most notably the continuing decline in the level of education in Algeria, the low level of research and development and the emergence of the bureaucratic nature of the user, in addition to the expulsion of human resources, primarily the scientific competencies that are at the heart of the knowledge economy. As well as the absence of a strategy for the information content industry, which is the most important component of the information society. Key Words : knowledge, Algeria, education, development, society, economy.